STRATEGI PENINGKATAN KINERJA PERSONIL RESERSE KRIMINAL DALAM MENANGANI PERKARA DI POLRES MAGELANG KOTA - Harry Dwi Purnomo; Sofiati Sofiati; Jazuli Akhmad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This research is a qualitative research. The informants in this study were 3 people, namely 1 Kaurmintu, 1 Kanit Idik 1 Crimea and 1 Police Personnel at the Criminal Investigation Unit of the Magelang City Police. Analysis of the data used in this study will be used with qualitative methods. Factors that have led to a decrease in the performance of the Sat Reskrim Polres Magelang personnel in dealing with cases are the limited competence of Polri investigators who have assistant investigator certificates; not all investigative personnel have the ability in the IT field; The intensity of work and reports from the public are many with the condition of limited investigative personnel; many whistleblowers do not properly understand the alleged case. Efforts to improve the performance of the Sat Reskrim Polres Magelang personnel in handling cases are (1) SO Strategy by increasing cooperation with the Regional Government and Central Java Regional Police as well as improving the quality and competence of investigators. (2) The WO strategy is to increase training in the field of investigation and then organize programs and activities in accordance with the main tasks and functions of the unit. (3) ST strategy, namely by increasing public understanding and improving communication with the community, by utilizing various media for outreach and counseling activities. (4) The WT strategy is to build and utilize an integrated information system and optimize the use of facilities and infrastructure in carrying out tasks.